Faculty Senate Minutes, September 17, 2015 - Faculty Senate, Valdosta State University (Valdosta State University Archives and Special Collections, 2015)
Valdosta State University Faculty Senate. "Faculty Senate Minutes, September 17, 2015." (Valdosta State University, 2014).
Keywords: Faculty Senate; Corporate minutes; Valdosta State University